Association of systemic corticosteroid use with prognosis of patients with acute exacerbations of chronic obstructive pulmonary disease in the intensive care unit: a propensity score-matched cohort study - Le Bai; Pengfei Zhu; Tingyu Pan; Yuanjie Liu; Yong Xu; Hailang He; Xianmei Zhou (BMC Medicine)
Abstract Background Systemic corticosteroid has been recommended for the treatment of severe acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Little is known about the use of systemic corticosteroid in patients admitted to intensive care units (ICU) since most of previous trials excluded these critically ill patients. Methods We conducted a matched cohort study based on the Medical Information Mart in Intensive Care-IV database. Patients with AECOPD in ICUs were included. Patients in the exposure group should be intravenously administrated with methylprednisolone or treated with oral prednisone within 24 h after ICU admission. The propensity score matching and multivariable analyses were used to adjust for covariates. The primary outcome was 28-day mortality, and secondary outcomes included ICU mortality, in-hospital mortality, the duration of ICU stay, and mechanical ventilation. Subgroup analyses for the primary outcome were performed according to age, sex, type of corticosteroid, type of ICU admission, type of mechanical ventilation, and co-morbidities/complications. Results The entire cohort and the matched cohort included 763 and 412 patients, respectively. In the matched cohort, the use of systemic corticosteroid had no impact on 28-day mortality (OR: 1.00, 95% CI: 0.61–1.64, P = 1.000). The results kept consistent in all subgroups. Additionally, systemic corticosteroid showed no benefits on ICU mortality, in-hospital mortality, the length of ICU stay, and the duration of mechanical ventilation. Conclusions The results of this study do not support routine use of systemic corticosteroid in patients with AECOPD admitted to ICUs.